Utilizing Teams-Game-Tournament (TGT) to Enhance Students’ Grammatical Understanding in Online Learning Setting - Kenti Sugiyati; Lilia Indriani (Universitas Tidar, 2022)
The massive implementation of online learning as a response to the pandemic over these past two years has offered abundant opportunities to explore, discover, and incorporate strategies for its execution and to cope with the possible challenges. Taking this into account, this present study is proposed to find out the effectiveness of an innovative pedagogical strategy namely teams-game-tournament as the type of cooperative learning model to teach grammar in an online learning setting. This study employed a quasi-experimental research design involving ten graders of senior high school (N=56). They come from two groups: the experimental group using teams-game-tournaments and the control group with only the traditional in-class lectures. The results obtained from the t-test using SPSS confirmed that there is a significant difference in students’ grammar scores that were taught using the strategy compared to students’ scores in the control group without the treatment. In order words, the use of the given strategy is more effective to enhance students’ English grammar, particularly in the correlative conjunction understanding.